Promoting Environment Sustainability Through Green HRM: The Socially Responsible Organizations - Subramanian, Padmavathy; Jaganathan, Ashok (Ushus Journal of Business Management, 2022)
The issue of global warming can be attributed to over usage of the environment and also because of the industrial revolution, which brought degradation to the world environment. Global warming has been causing a negative impact on the industries, and these worries have created more strain on the organizations. These organizations have started to practice environmentally-pleasant methods and also started producing products that are environment-friendly. These environmental protection measures were used to control means of practicing environment-friendly measures in different departments such as production, finance, advertising and marketing and others. Recently, Human Resource Management has also joined this group, and now Green Human Resource Management (GHRM) has also started to gain importance. GHRM assists in improving Environmental Performance (EP) growing through personnel dedication which is closer to the environment.